2009
DOI: 10.1002/elan.200804388
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free Detection of DNA Hybridization in Presence of Intercalators Using Electrochemical Impedance Spectroscopy

Abstract: Actinomycin D or proflavine which are known to intercalate within the helix of double-stranded DNA (dsDNA) are used as label-free control to unequivocally prove complementary DNA hybridization by means of electrochemical impedance spectroscopy (EIS). Based on a carefully designed interface comprising a thiol-tethered (20mer) oligonucleotide capture probe which forms a self-assembled monolayer on a gold electrode together with a short chain hydroxyl-terminated alkylthiol, formation of dsDNA can be monitored by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 38 publications
(32 reference statements)
2
57
0
1
Order By: Relevance
“…The obtained electrodes were further incubated with proflavine as specific intercalator for dsDNA, as previously reported. [28] The decrease of the concentration of the MCH molecules co-assembled at the gold electrode endows an increase of R ct when the hybridization was carried out for 1.5 h. A hybridization time of only 45 min did not reveal significant changes in the R ct (Figure 2 B). This tendency is even more pronounced at higher dilutions of MCH in the monolayer (Figures 2 C, D).…”
Section: Post-assembly Of Mercaptohexanolmentioning
confidence: 92%
See 1 more Smart Citation
“…The obtained electrodes were further incubated with proflavine as specific intercalator for dsDNA, as previously reported. [28] The decrease of the concentration of the MCH molecules co-assembled at the gold electrode endows an increase of R ct when the hybridization was carried out for 1.5 h. A hybridization time of only 45 min did not reveal significant changes in the R ct (Figure 2 B). This tendency is even more pronounced at higher dilutions of MCH in the monolayer (Figures 2 C, D).…”
Section: Post-assembly Of Mercaptohexanolmentioning
confidence: 92%
“…layers; [28,29] iv) the roughness of the electrode surface, which determines the packing density in the SAM; [30,31] v) the Debye length, which reflects the decay length of the electric field and is a measure of the counterion screening; and vi) the electric field in front of the electrode surface and the formation of the electrochemical double layer. [32] It has been shown that the orientation of grafted DNA strands can be efficiently controlled by the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…DNA biosensors probe and/or detect the hybridization event, which is then transduced, for example, into an electrochemical [17][18][19][20][21][22] or optical [23][24][25][26] signal (Figure 3). In principle, an analytical sample, which contains, amongst others, the DNA sequence-of-interest (the target), is deposited onto the recognition layer of a transducer.…”
Section: Metal-containing Pnas For Biosensing Purposesmentioning
confidence: 99%
“…Indirect labels like intercalating molecules can offer a useful compromise between easier sample preparation and improved detection sensitivity, whereby direct labelling of the target nucleic acid sequence is not required. have also been used in conjunction with EIS to serve as signal validation tools to exclude potential false positives by non-specific adsorption [20,21]. These molecules cause a decrease in R ct upon binding to dsDNA, but cause little or no change with ssDNA.…”
Section: Introductionmentioning
confidence: 99%